Identifikasi Tingkat Partisipasi Masyarakat dalam Pengembangan Desa Wisata Lamajang Kabupaten Bandung - Faizal Hamada; Gina Puspitasari (Bandung Conference Series: Urban & Regional Planning, 2022)
Abstract. Tourism is one of the leading sectors that contributes the highest foreign exchange in Indonesia. Tourism activities are unlikely to be successful if there is no participation from the community. Lamajang Village is one of the villages in Indonesia which has been a tourism village since 2011. The purpose of this study was to determine the level of community participation in the development of the Lamajang Tourism Village. The method used is quantitative descriptive statistics with scoring analysis methods and participation rate analysis. From the results of the analysis, it can be concluded that the level of participation of the people of Lamajang Village is high, seen from the 4 stages, namely the planning stage of 92%, the implementation stage of 85.4%, the utilization stage of the results of 87%, the evaluation stage of 81% and the average percentage of participation. the average is 86.25%. However, the enthusiasm of the community has not been optimally supported by the village government in terms of funding so that the development of the Lamajang Tourism Village has not been optimal. Abstrak. Pariwisata merupakan salah satu sektor unggulan penyumbang devisa tertinggi di Indonesia. Kegiatan Pariwisata tidak mungkin berhasil apabila tidak adanya partisipasi dari masyarakat. Desa Lamajang salah satu desa di Indonesia yang merupakan Desa Wisata sejak tahun 2011. Tujuan dari penelitian ini yaitu untuk mengetahui tingkat partisipasi masyarakat dalam pengembangan Desa Wisata Lamajang. Metode yang digunakan yaitu statistik deskriptif kuantitatif dengan metode analisis skoring dan Analisis tingkat partisipasi. Dari hasil analisis dapat disimpulkan bawah tingkat partisipasi masyarkat Desa Lamajang yaitu tinggi, dilihat dari 4 tahapan yaitu tahap perencanaan sebesar 92%, tahap pelaksanaan sebesar 85,4%, tahap pemanfaatan hasil sebesar 87%, tahap evaluasi sebesar 81% dan persentase partisipasi rata-rata yaitu sebsar 86,25%. Namun, antusias masyarakat tersebut belum didukung secara optimal oleh pemerintah desa dari segi pendanaan sehingga, pengembangan Desa Wisata Lamajang belum optimal.